An Analysis of Code-Switching at A Public Place - Komang Indah Permatasari (Jurnal Penelitian Mahasiswa Indonesia, 2022)
This research aimed to observe the code-switching at a public place. In the code-switching observed, the researcher describes the types of the code-switching that dominantly occur in the seller and buyer’s conversation. The observation has done at Pasar Banyuasri Singaraja in 61 interlocution and described into several subjects; male and female. The data from the observation was collected using some instruments such as human instrument, audio-recorder, transcription and data tabulation. The data was described using Wardhaugh’s (1998) theory of code-switching. The result of this research shows that there are two types of code-switching found in the sellers and buyers’ interlocution. Those types are inter-sentential and intra-sentential. The result showed that inter-sentential is 41% from the utterances, while intra-sentential is 51% from the utterances. Therefore, the most of dominant type of code-switching observed at Pasar Banyuasri Singaraja is intra-sentential which is come from 527 utterances. While inter-sentential came from 368 utterances. The languages that were used to be inserted and switched are Indonesian, Balinese, English, and Javanese language.